Independent Prognostic Value of MRproANP (Midregional Proatrial Natriuretic Peptide) Levels in Patients With Stroke Is Unaltered Over Time. Issue 6 (June 2020) - Arnold, Markus; Nakas, Christos; Luft, Andreas; Christ-Crain, Mirjam; Leichtle, Alexander; Katan, Mira
Abstract : Background and Purpose—: MRproANP (midregional proatrial natriuretic peptide) is known to be independently associated with cardioembolic stroke cause and to improve risk stratification for 90-day mortality when measured within 24 to 72 hours after symptom onset in patients with acute ischemic stroke. However, the optimal time point for assessment remains unclear. This study aimed to evaluate prognostic utility of MRproANP at different time points during the first 5 days of hospitalization in patients with acute ischemic stroke. Methods—: Samples of MRproANP were collected on admission (<72 hours after onset) and at multiple time points during the first 5 days of hospitalization in 348 consecutively enrolled patients with acute ischemic stroke. The prognostic value for 90-day mortality, 90-day functional outcome, and the association with cardioembolic stroke cause was assessed regarding the time of measurement, and change over time was modeled using generalized estimating equations. Results—: MRproANP levels modestly decease over the initial 5 days but remain highly predictive for cardioembolic stroke cause (odds ratio, 9.75 [95% CI, 3.2–29]; 10.62 [95% CI, 3.4–33.3]; 10.8 [95% CI, 3.1–37.1]; 19.4 [95% CI, 5.49–68.7] on admission, day 1, 3 and 5) and 90-day mortality (odds ratio, 59.4 [95% CI, 7.4–480.7]; 78.3 [95% CI, 7.9–772.6]; 14.5 [95% CI, 1.4–145]; 19.81 [95% CI, 2.7–143.4] on admission, day 1, 3, and 5). Change over time does not significantly modify the prognostic value of MRproANP ( P =0.65 and P =0.56 for the interaction term in the multivariate model). Conclusions—: Independent prognostic value of MRproANP remains unaltered in the acute phase of stroke at least up to 5 days; repeated measurements do not improve the prognostic value. Abstract : Supplemental Digital Content is available in the text.